An Analysis of the Expansion and Potential of Agribusiness in India (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to investigate the growth and future prospects of agriculture in India by looking at current trends, environmentally responsible growth strategies, and the social effects of these factors. The study, which is based on a survey, highlights the importance of comprehending and resolving current issues in the agriculture industry and illuminates the perspectives of stakeholders. If the implications are effectively implemented, they may result in more ecologically friendly practices, a narrowing of socioeconomic divides, and inclusive rural development. The abstract also highlights the social significance and transformative potential of aligning agribusiness expansion with broader societal goals.